Assessment of Neighbor‐Initiated Risks in an Integrated Air Separation Unit‐Gasification Facility. Issue 3 (10th January 2019) - Cialkowski, Edward J; Li, Yuqiang
Abstract : Gasification facility operators increasingly find it cost effective to outsource the supply of industrial gases, such as oxygen and nitrogen, to companies with a proven track record for designing and operating safe and reliable air separation unit (ASU) equipment. Air Products have built & operated many such ASU facilities in recent years and supplied industrial gases to customers directly by pipeline, with long term supply partnerships. Most of these ASU facilities are located within the customer boundary and are effectively integrated with customer gasification facilities. In addition to any risks that the ASU may pose to the customer's operations or personnel, there may be significant hazards originating with the customer's equipment or processes that pose a risk to the ASU personnel. Air Products developed an approach to assessing risks from neighboring facilities to the ASU equipment and personnel. The focus of this article is on the work process and sequence of steps used to develop a risk assessment and mitigation plan. Overall safety and risk management is improved by sharing hazard information between the industrial gas supplier and the customer, as well as developing a joint emergency response program. © 2019 American Institute of Chemical Engineers Process Saf Prog 38: e12032, 2019